Chaotic synchronization of vibrations of a coupled mechanical system consisting of a plate and beams - J. Awrejcewicz; A.V. Krysko; T.V. Yakovleva; D.S. Zelenchuk; V.A. Krysko (Latin American Journal of Solids and Structures)
In this paper mathematical model of a mechanical system consisting of a plate and either one or two beams is derived. Obtained PDEs are reduced to ODEs, and then studied mainly using the fast Fourier and wavelet transforms. A few examples of the chaotic synchronizations are illustrated and discussed.